A numerical study of NOx and soot emissions in methane/n-heptane triple flames. (October 2018) - Sabnis, Prithviraj; Aggarwal, Suresh K.
Abstract: There is significant interest worldwide in using cleaner/renewable fuels, such as syngas and biogas, in transportation and power generation systems. We report herein a computational study to investigate NOx and soot emissions in n-heptane/methane triple flames in an opposed-jet configuration. The objective is to evaluate various fuel injection scenarios in a dual-fuel engine using a simple configuration to emulate important aspects of diesel combustion. Simulations are performed by combining a detailed fuel and NOx chemistry model with a soot model. Three blending strategies are examined. For each strategy, NOx, PAH and soot emissions, and thermal efficiency are characterized by varying the energy content between the two fuels, while keeping the total energy input rate fixed. As methane in the blend is increased, the benzene emission index and soot emission decrease with all three strategies, but the reduction is more pronounced with strategies 2 and 3. In addition, it leads to higher efficiency with strategies 2 and 3, but lower efficiency with strategy 1. Thus strategy #1 yields higher NOx, PAH and soot emissions, and lower efficiency compared to other two strategies, and is not recommended. Highlights: Evaluation of various fuel injection strategies relevant to dual-fuel engine. Flame simulation to emulate important aspects of diesel combustion. Use of a fuel and NOx chemistry model combined with a detailed soot model. NOx, PAH, and soot emissions in methane/n-heptane triple flames. Significant reduction in PAH and soot emissions using dual-fuel blending strategies.